Analisis Kepribadian Anak terhadap Pola Asuh Orang Tua yang Bekerja Penuh Waktu dan Orang Tua yang berada di Rumah - Christina Anugerah; Gloria Jesika Tampubolon; Vanessha Dini Olivia Sipayung; Hairani Siregar (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Parents are the main educational figures for children. The presence of parents is fundamental to the development of a child's personality, but this alone is not enough. What is important for the development of a child's personality is the nature of the relationship between parents and children, as well as the emotional bond between them. This study was conducted to investigate differences in children's personalities between families with parents who work full-time and those who stay at home. The study targeted adolescents aged 17 to 25 years using a quantitative survey method through the distribution of an online questionnaire via Google Forms. Respondents were selected using purposive sampling. The data obtained were then analyzed to produce numerical values or variables. The results of this study indicate that children with stay-at-home parents tend to have high self-confidence. This is supported by findings showing that 25 respondents stated that parental roles significantly influence the development of a child's behavior. These findings suggest that children's personalities are highly dependent on the parenting styles adopted by their parents.